2021
DOI: 10.1002/jbm.b.34867
|View full text |Cite
|
Sign up to set email alerts
|

Comparison capacity of collagen hydrogel, mix‐powder and in situ hydroxyapatite/collagen hydrogelscaffolds with and without mesenchymal stem cells and platelet‐rich plasma in regeneration of critical sized bone defect in a rabbit animal model

Abstract: The aim of this study was to investigate the effect of developed collagen (Co) hydrogel (CH), powder-mixed hydroxyapatite/collagen (HA/Co) hydrogel and in situ synthesized HA/Co (In/HA/Co) hydrogel with or without mesenchymal stem cell (MSC) and platelet-rich plasma (PRP) on the regeneration of fullthickness critical size bone defect in the rabbit animal model. In the first step of this study, the scaffolds were synthesized and characterized using FTIR spectroscopy, X-ray diffraction, and scanning electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It is worth mentioning that the C and CG groups also showed limited osteogenic effects in both 2D and 3D culture models (Figures 4B–F and 5B–E) without obvious macrophage polarization toward M2, which was consistent with previous studies. [ 27a,30 ] As reported, type I collagen, acting as a regulator of osteogenic differentiation and cell adhesion, [ 27b,31 ] has the ability to guide a development toward the bone cell phenotype, [ 27c ] which may be partially achieved by modulating the [Ca 2+ ] i‐ and cAMP‐signaling pathways through altering PCK activity. [ 32 ] Collectively, these data suggest that macrophage polarization by magnetized hydrogels under an MF effectively promoted BMSC osteogenic differentiation, which shows potential in the development of novel immunomodulatory approaches for bone regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that the C and CG groups also showed limited osteogenic effects in both 2D and 3D culture models (Figures 4B–F and 5B–E) without obvious macrophage polarization toward M2, which was consistent with previous studies. [ 27a,30 ] As reported, type I collagen, acting as a regulator of osteogenic differentiation and cell adhesion, [ 27b,31 ] has the ability to guide a development toward the bone cell phenotype, [ 27c ] which may be partially achieved by modulating the [Ca 2+ ] i‐ and cAMP‐signaling pathways through altering PCK activity. [ 32 ] Collectively, these data suggest that macrophage polarization by magnetized hydrogels under an MF effectively promoted BMSC osteogenic differentiation, which shows potential in the development of novel immunomodulatory approaches for bone regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…Hydroxyapatite has similarities to bone tissue and is widely applied as a grafting material in bone regeneration surgeries due to its excellent biocompatibility and osteoconductive characteristics [8,[16][17][18]. Beta tricalcium phosphate is one of the most attractive bone repair materials for regenerative areas, has excellent osteoconductive and osteotransductive properties, and has a crystalline structure of simple degradation and thermal stability [1,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are some controversial results of platelet-rich preparations on the regenerative processes of bone tissue [193,194], in general, recent reports show a beneficial effect of PRP in combination with biomaterials on the regeneration of bone tissue (Figure 9). It was found that biomaterials enriched with platelet-rich preparations promoted the adhesion, viability, proliferation and osteogenic differentiation of osteoblasts and stem cells.…”
Section: Bone Biomaterials Enriched With Prpmentioning
confidence: 99%
“…Thus, these promising in vitro results showed that the addition of PRP to the CDHA/collagen scaffold promoted its cytocompatibility and osteogenic potential; however, additional in vivo research should be performed in order to confirm this phenomenon. Bakhtiarimoghadam et al [194] developed collagen/powder mixed HAp (HAp/Col) and in situ synthesized a collagen/hydroxyapatite hydrogel (In/HAp/Col), and they evaluated their biocompatibility in vivo with or without the addition of rabbit BMSCs and PRP. The study was performed by using New Zealand rabbits with full-thickness critical-size radial bone defects.…”
Section: Bone Biomaterials Enriched With Prpmentioning
confidence: 99%